Development and validation of a novel high-performance liquid chromatography (HPLC) method for the detection of related substances of pralsetinib, a new anti-lung cancer drug - Zhu, Yonghong; Qin, Jisu; Wu, Wenyi; Cai, Liangliang (Frontiers in Chemistry, 2024)
Background: Pralsetinib, a targeted inhibitor of the RET enzyme, plays a critical role in the treatment of adult patients with locally advanced or metastatic non-small cell lung cancer (NSCLC) characterized by RET gene fusion mutations following platinum-based chemotherapy. Nevertheless, impurities resulting from the manufacturing and degradation of pralsetinib have the potential to impact its therapeutic effectiveness and safety profile.Methods: To address this issue, a liquid chromatography method was developed and validated for the specific identification of pralsetinib and its related impurities. The separation of pralsetinib and its related impurities was achieved via a Waters X Bridge C18 column with dimensions of 4.6 mm × 250 mm and a particle size of 5 μm. Mobile phase A was composed of 20 mmol/L potassium dihydrogen phosphate (KH2PO4) and acetonitrile (ACN) at a volume ratio of 19:1, while mobile phase B consisted solely of ACN, utilizing a gradient elution technique. Detection was performed at a wavelength of 260 nm, with an injection volume of 10 μL and a flow rate of 1.0 mL/min.The chromatographic method established in this study was validated according to the ICH Q2 (R1) guidelines. The method demonstrated excellent linearity over a specific concentration range (imp-A